THE CONCEPT OF TRANSFORMATIONAL LEADERSHIP IN EDUCATIONAL INSTITUTION LEADERS - Muhammad Ardli Mubarok; Desy Islamiati (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
Leaders in educational institutions play a crucial role in the development of these institutions. Consequently, a leader must possess a genuine spirit of leadership. Transformational leadership focuses on efforts to inspire, motivate and develop team members in order to bring about positive change within the organisation. This type of leadership involves leaders who are able to articulate a clear vision, create an environment that supports innovation, and attend to the needs of individuals so that they can reach their full potential. This study aims to explore and understand the nature of transformational leadership. It employs a descriptive and analytical approach through a comprehensive literature review to collect, sort, and analyse relevant literature. The findings indicate that the key characteristics of transformational leadership comprise four main components: idealised influence, inspirational motivation, intellectual stimulation, and individualised consideration. It is hoped that this research will provide in-depth insights into leadership theory and offer guidance to practitioners on enhancing leadership effectiveness within their organisations.